Immediate/Early vs. Delayed Invasive Strategy for Patients with Non-ST-Segment Elevation Acute Coronary Syndromes: A Systematic Review and Meta-Analysis - Li, Yanda; Zhang, Zhenpeng; Xiong, Xingjiang; Cho, William C.; Hu, Dan; Gao, Yonghong; Shang, Hongcai; Xing, Yanwei (Frontiers in Physiology, 2017)
Invasive coronary revascularization has been shown to improve prognoses in patients with non-ST-segment elevation acute coronary syndromes (NSTE-ACS), but the optimal timing of intervention remains unclear. This meta-analysis is to evaluate the outcomes in immediate (<2h), early (<24h) and delayed invasive group and find out which is the optimal timing of intervention in NSTE-ACS patients. Studies were identified through a computerized literature search of Medline, PubMed Central, Embase, the Cochrane Library and CNKI. Data were extracted for populations, interventions, outcomes, and risk of bias. All-cause mortality was the prespecified primary end point. The longest follow-up available in each study was chosen. The odds ratio(OR) with 95% CI was the effect measure. In the comparision between early and delayed intervention, we found that early intervention led to a statistical significant decrease in mortality rate (n = 6624; OR 0.78, 95% CI: 0.61–0.99) and refractory ischemia (n = 6127; OR 0.50, 95% CI: 0.40–0.62) and a nonsignificant decrease in MI, major bleeding and revascularization. In the analysis comparing immediate and delayed invasive approach, we found: immediate intervention significantly reduced major bleeding (n = 1217; OR 0.46, 95% CI: 0.23–0.93) but led to a nonsignificant decrease in mortality rate, refractory ischemia and revascularization and a nonsignificant increase in MI. In conclusion, early invasive strategy may reduce the risk of refractory ischemia, while immediate invasive therapy shows a benefit in reducing the risk of major bleeding. In addition, immediate invasive therapy may lead to a lower mortality rate, however, this conclusion is not stable.